Screening and isolation of novel quorum sensing inhibitors against clinical pseudomonas aeruginosa from indian Marine algae ulva-rigida. - EAZHIL NAMBI.A; K.G.PURUSHOTHAM; SHANMUGHA SUNDHAR.D (International Journal of Pharma and Bio Sciences, 2018)
Bacterial biofilms which are mediated by mechanism of quorum sensing are prevalent in biological systems such as gastrointestinal, respiratory and reproductive tracks, industrial and environmental system such as purification membranes and treatment tanks and in most ecosystem. The shielding and maturation of such biofilms are becoming hard to treat in case of nosocomial infections as chemical disruptive agent used for industrial biofilm eradication have increased toxicity .Therefore the search for novel biofilm inhibitors for treatment and eradication of disease or infection associated biofilms are on the rise. Recent approaches have shifted towards identifying biomolecules that have good biofilm inhibition potential and can be clinically exploited, from plant, fungal and other sources. Invasive marine algal species are well known for their ability to inhibit and deteriorate bacterial communities as well as biofilms. Very few studies are there for understanding the mechanism of quorum sensing inhibition by potential algal compounds. Ulva rigida is an invasive marine macro algae that is reported to have excellent biofilm inhibition properties. However, the chief compounds responsible for quorum sensing inhibition activity are not well established. The current study focuses on screening and isolation of novel quorum sensing inhibitor compounds that are analogues of AHL molecules form Ulva rigida thereby targeting biofilm inhibition in biofilm associated Pseudomonas aeruginosa infections or diseases. Crystal violet assay and violacein unit assay confirmed the presence of biofilm inhibition components in ethyl acetate (45%) and methanolic (85%) extracts of Ulva rigida at 0.25 mg/ml. Column chromatography and purification of obtained by solvent treatment were performed for methanolic extract. GC-MS analysis revealed the presence of Anthracenedione (80.4%) in the bioactive fraction. However checkerboard assay shows synergistic effect between ethyl acetate and methanolic extracts. Further investigation on identifying the potent biofilm inhibitors and underlying mechanisms are required to obtain novel biofilm inhibitors that can be used for clinical treatment.